The relative stability of the European money demand function: The portfolio diversification effect - Nikolaus K. A. Läufer (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
The hypothesis of the paper that the European money demand function is more stable than the money demand function of any single European country is based on the well known portfolio diversification principle. Econometric estimates of country specific and European money demand functions confirm the hypothesis for M1, and, with some qualifications, also for M3. The tests also confirm the portfolio theoretical reason given for the higher stability.
Keywords: 330; Geldnachfrage; Portfolio-Management; EU-Staaten